PENINGKATAN KETERAMPILAN PROSES SAINS MELALUI PERCOBAAN SEDERHANA ANAK USIA 5-6 TAHUN DI TK-IT ALBINA TERNATE - Santi M. J. Wahid; Slamet Suyanto (Universitas Negeri Yogyakarta, 2015)
This research is aimed to find out the improvement of the science skill through the simple experiment for the 5-6 year-old students in TK IT Albina, Ternate. This research was a Classroom Action Research (collaborative) consisted of three cycles with six meetings. The subjects of the research were the students of Class B2 in TK IT Albina Ternate which were 19 students consisting of 8 boys and 11 girls. The data collection techniques were by observing and making field notes. The instruments of the research used the students Science Process Skills (SPS) observation sheets and teacher observation sheets during the process of studying. The data then were analyzed by using descriptive qualitative and quantitative methods. The results of this research indicats the improvement of science process skill entirely in the Cycle I is 59.38 %, in Cycle II is 66.12%, and in Cycle III is 78.82% with each SPS indicator as (1) SPS made judgment is 53.84%, 60.53%, 73.55%, (2) SPS observing is 65.02%, 71.71%, and 85%, (3) SPS classifiying is 64.25%, 69.08%, 84.01%, and (4) SPS communicating is 54.39%, 63.08%, 72.70%. In Cycle I The teacher's activities improve from 36.84% to 47.37%, in Cycle II much as 63,16% and 73.68%, and in cycle III is 89.47%.